Measurement of the tt production cross section in pp collisions at square root s = 1.96 TeV using missing E(T) + jets events with secondary vertex b tagging. - Abulencia, A; Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2006)
We present a measurement of the tt production cross section in pp collisions at square root s = 1.96 TeV which uses events with an inclusive signature of significant missing transverse energy and jets. This is the first measurement which makes no explicit lepton identification requirements, so that sensitivity to W --> tau nu decays is maintained. Heavy flavor jets from top quark decay are identified with a secondary vertex tagging algorithm. From 311 pb(-1) of data collected by the Collider Detector at Fermilab, we measure a production cross section of 5.8 +/- 1.2(stat)(-0.7)(+0.9)(syst) pb for a top quark mass of 178 GeV/c2, in agreement with previous determinations and standard model predictions.